Implementasi Metode Jama’ Berbantu Media Audio Pada Program Hapalan Qur’an Siswa di MAN Pematang Siantar - Tika Wulan Sari; Junaidi Junaidi (Universitas Labuhanbatu, 2023)
The background of this research is that there are still many students who often forget to memorize the Qur'an due to lack of concentration. Therefore, researchers want to conduct research to determine the effectiveness of the methods and tools used in implementing the Qur'an memorization program at MAN Pematangsiantar. The formulation of the problem discussed in this research is how to plan, implement, and overcome the obstacles faced in implementing the Qur'an memorization program using the jama` method assisted by audio media at MAN Pematangsiantar. The aim of this research is to find out how the planning process, implementation, and obstacles faced during the Qur'an memorization program using the jama` method assisted by audio media were implemented. This type of research is qualitative research using a descriptive approach. This means that the data collected is not in the form of numbers but rather in the form of interview scripts, field notes, and pictures. To obtain accurate data, researchers used data collection techniques in the form of observation, interviews, and documentation. Research analysis used by researchers involves data reduction, data presentation, and drawing conclusions. The research results obtained are as follows: Planning the Qur'an memorization program at MAN Pematangsiantar is an activity of determining a series of activities that will be carried out in order to achieve the goal and determining the methods that will be used, time/schedule of activities, and content/material of activities so that the program runs well and does not interfere with the student learning process. The implementation of the Qur'an memorization program at MAN Pematangsiantar using the jama` method assisted by audio media is currently running quite well, and the method used is deemed appropriate to assist students in implementing the Qur'an memorization program. The obstacles faced during the process of implementing the Qur'an memorization program using the jama` method are that students often forget the verses they previously memorized. The timing of implementing the Qur'an memorization program is also an obstacle because it is feared that it will disrupt the student's learning process.